The study of obesity among children aged 5-18 years in Jaipur, Rajasthan - Anjali Jain; Ashish Jain; J P Pankaj; B N Sharma; A Paliwal (Wolters Kluwer Medknow Publications, 2016)
Background: Prevalence of TV and computers in today's times has also driven the regular outdoor activities of children out from their lives. An increased calorie intake along with a decreased physical activity level has a great bearing on the level of obesity found in children. The present study was done with the objective to study the obesity among children of aged 5-18 years in Jaipur, Rajasthan. Methods: A Cross sectional study was undertaken on children of 5-18 years of urban field practice area, Mahatma Gandhi Medical College and Hospital, Jaipur. Simple random sampling was done. A semi-structured questionnaire was developed, pilot study was carried out to draw the necessary questionnaire which was tested and retested for necessary modifications. Body Mass Index (BMI) 10 was derived by dividing the subject's mass by the square of his or her height, Statistical test was applied in our study accordingly. Results: 12.5% children were overweight having percentage between 85 to 95, while only 5.6% children were obese having percentage equal or greater than 95. Out of 564 boys 101 (17.9%) were obese or over-weight and out of 436 boys 69 (15.9%) were obese or over-weight. Among 783 vegetarian children, 14.8% were obese and overweight. Conclusions: Children eating more frequent junk foods were more obese and overweight as comparative eating them in low frequency. Children with lesser physical activity were more obese.